The pharmacology and therapeutic potential of small molecule inhibitors of acid-sensing ion channels in stroke intervention - Leng Tian-dong; Xiong Zhi-gang (Acta Pharmacologica Sinica, 2016)
Tian-dong LENG, Zhi-gang XIONG* Neuroscience Institute, Morehouse School of Medicine, Atlanta, GA 30310, USA In the nervous system, a decrease in extracellular pH is a common feature of various physiological and pathological processes, including synaptic transmission, cerebral ischemia, epilepsy, brain trauma, and tissue inflammation. Acid-sensing ion channels (ASICs) are proton-gated cation channels that are distributed throughout the central and peripheral nervous systems. Following the recent identification of ASICs as critical acid-sensing extracellular proton receptors, growing evidence has suggested that the activation of ASICs plays important roles in physiological processes such as nociception, mechanosensation, synaptic plasticity, learning and memory. However, the over-activation of ASICs is also linked to adverse outcomes for certain pathological processes, such as brain ischemia and multiple sclerosis. Based on the well-demonstrated role of ASIC1a activation in acidosis-mediated brain injury, small molecule inhibitors of ASIC1a may represent novel therapeutic agents for the treatment of neurological disorders, such as stroke. Keywords: ion channels; acidosis; ASIC; proton; stroke; neurological disorders The work in Dr Zhi-gang XIONG’s laboratory was partially supported by NIH R01NS047506, R01NS066027, NIMHD S21MD000101, U54 RR026137, AHA 0840132N, and ALZ IIRG-10-173350. * To whom correspondence should be addressed. E-mail zxiong@msm.edu Received 2012-04-23 Accepted 2012-05-22